Legalitas Poligami dan Nikah Siri: Analisis Kritis Disharmoni Hukum Pidana dalam Dinamika Hukum Keluarga Islam - Asman (Al Fuadiy Jurnal Hukum Keluarga Islam, 2026)
This study critically examines the approval of the Republic of Indonesia's Law No. 1 of 2023 on the Criminal Code (KUHP) as evidence of a growing paradigm change in the national criminal law, particularly in those areas that have historically fallen under the purview of family and religious law. The author sees this phenomenon as a kind of state expansion (penal expansion) that has the potential to create structural tensions between the criminal law of the nation, the core tenets of Islamic family law, and the constitutional protections for religious freedom and the practice of religious teachings for its people. The novelty of this study lies in its integrated and critical approach, which examines the legitimacy of polygamy and nikah siri practices from a fiqh munākaḥāt perspective while also using the uṣūl al-fiqh and maqāṣid al-syarī'ah frameworks to evaluate the criminalization scheme in the KUHP 2023. As a result, the study examines the systemic reasoning behind criminalization, which ignores the distinction between administrative infractions and criminal offenses (jarīmah), rather than merely describing the conflict of norms. Using a normative legal approach with legislative, conceptual, and Islamic legal components, this study analyzes the law. The author strongly argues that the KUHP 2023's regulation of polygamy and nikah siri reveals a normative conflict with fundamental Islamic family law principles, particularly in relation to the validity of the contract, the goals of marriage, and the protection of the public welfare. The research findings support the idea that criminalizing legitimate religious practice under syariah law has the potential to result in excessive criminalization and violate the principles of substantive fairness and proportionality in criminal law.The study makes a significant academic contribution by formulating a family criminal law reconstruction model that prioritizes welfare by advocating for a shift from criminal punishment to administrative sanction mechanisms and the protection of rights. This model is put forth as a normative alternative that is more in line with the precepts of Islamic law, the constitution, and the humanistic, plurality-sensitive path of national law reform in Indonesia.